Overview of law of torts - Gupta, RK (Delhi, 1982)
The law of torts deals with wrongs independent of contract, for which the appropriate remedy is an action for damages. The law of torts is not codified in India and the courts apply the principles evolved by British Courts which are applicable to Indian conditions. However new principles are enuciated by the courts, in cases where English law does not meet the ends of justice.
Keywords: Torts